2017
DOI: 10.17507/jltr.0802.03
|View full text |Cite
|
Sign up to set email alerts
|

Teaching EFL in Saudi Arabian Context: Textbooks and Culture

Abstract: Abstract-This article analysed the impact of foreign (L2) cultures on EFL students in Saudi universities. The investigation has been carried out on the basis of theoretical background study, an analysis of the prescribed textbooks and a survey of the L2 learners' attitudes. The research samples include two course books, Access and Interaction1 published by McGraw-Hill Education, and students of English Department, Najran University, KSA. A thorough analysis of the contents of the series showed that the textboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Some pictures, depending on the instructors' opinions, should be revised and modified to suit the local culture of the students. This result of findings supported what had obtained by Ahmad and Shah (2014) and Aldera (2017) who found that the textbooks ignored the Saudi culture and included mainly foreign cultures. Objectives, according to Table 3, were considered to be appropriate and applicable.…”
Section: Findings Of the Studysupporting
confidence: 91%
“…Some pictures, depending on the instructors' opinions, should be revised and modified to suit the local culture of the students. This result of findings supported what had obtained by Ahmad and Shah (2014) and Aldera (2017) who found that the textbooks ignored the Saudi culture and included mainly foreign cultures. Objectives, according to Table 3, were considered to be appropriate and applicable.…”
Section: Findings Of the Studysupporting
confidence: 91%
“…For example, some EFL teachers perceive teaching cultural values as a form of cultural imposition or, more accurately, as a form of linguistic globalization emanating from cultural globalization. Teachers who view instruction in culture as a covert way of imposing cultural hegemony or linguistic imperialism fear that teaching Western values or Anglo-American cultural practices is liable to alienate students from their own cultural values and erode their identities owing to the non-representation of their own context (Al-Dosari, 2013;Al-Samani, 2014;Al-Seghayer, 2016;Aldera, 2017). Some teachers also believe that teaching non-local culture may diminish students' motivation or, worse still, encourage them to adopt cultural values associated with the English language.…”
Section: Underlying Factors Behind Current Saudi Efl Teachers' Approaches To Teaching Cultural Knowledge In Saudi Efl Classroomsmentioning
confidence: 99%
“…Despite the importance of improving EFL writing skills, the EFL learners in general and EFL Saudi learners in particular do not focus upon these skills. Previous studies in the Saudi context mostly focused on analyzing English textbooks by using the CA analysis approach without giving ample attention to the learners' perception such as (Aldera, 2017;Almujaiwel, 2018). Mostly, in the EFL countries including Saudi Arabia, success in English at schools and universities is measured depending on the accuracy of their writing products.…”
Section: Problem Statementmentioning
confidence: 99%